A formação docente e sua importância para a educação profissional e tecnológica no IFAM-Campus Coari - Silva, Robson Freitas da (2019)
This work aimed to analyze the formative processes experienced by the teaching staff of the technical course in administration, as integrated with the high school of the Federal Institute of Amazonas, Coari campus, identifying the alignment of these processes with the Professional and Technological Education. For this purpose, a study of the legal landmarks of professional and technological education was also developed, with emphasis on the requirements for teacher training. This is a research developed in the scope of the Master in Professional and Technological Education (ProfEPT) that had as methodological theoretical basis the Case Study developed from the proposal of Yin (2005) which allowed the researcher to deepen the phenomenon studied. The main instruments for data collection were the application of questionnaires and semi-structured interviews, preceded by bibliographic review and documentary research. The theoretical foundation used for the analysis of teacher education processes is based on the teaching knowledge present in the studies by Tardif (2014). The research results guided the development of an educational product in the form of two Pedagogical Teacher Training Workshops elaborated in the perspective of providing a space for reflection, discussion and creation of alternatives for the teaching work through the exchange of experiences and based elements as the “Integral Human Formation” and “Work as an Educational Principle” that compose the EPT Theoretical bases.